2017
DOI: 10.1007/s00330-017-5020-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective collateral circulation may indicate improved perfusion territory restoration after carotid endarterectomy

Abstract: • Evaluation of collaterals before CEA is helpful for avoiding ischaemia during clamping. • There was good agreement on ATA-based ASL collateral grading. • Perfusion territories in carotid stenosis patients are altered. • Patients have better collateral circulation with perfusion territory back to normal. • MMSE and MOCA test scores improved more in the territory normalisation group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…More and more studies have confirmed that cerebral vascular stenosis first leads to hypoperfusion in the perfusion territory, while increasing cerebral collateral circulation to compensate for impaired cerebral blood flow, and carotid endarterectomy and carotid stent can significantly improve rCBF Fig. 1 The cubic simulation curve between TSS and GBF (a), and between RI-TSS and GBF (b) in the perfusion territory [14][15][16]. However, the effects of these local vascular stenosis on GBF and the relationship between degree of carotid stenosis and GBF have not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…More and more studies have confirmed that cerebral vascular stenosis first leads to hypoperfusion in the perfusion territory, while increasing cerebral collateral circulation to compensate for impaired cerebral blood flow, and carotid endarterectomy and carotid stent can significantly improve rCBF Fig. 1 The cubic simulation curve between TSS and GBF (a), and between RI-TSS and GBF (b) in the perfusion territory [14][15][16]. However, the effects of these local vascular stenosis on GBF and the relationship between degree of carotid stenosis and GBF have not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…CBF is an important parameter that determines the condition of the brain. Increased CBF indicates potential increased brain activity, and a pathological decrease in CBF can immediately cause reversible or irreversible damage to brain tissue 17 . A previous study has reported that DSA may force some physiologically closed shunts to open due to the injection pressure of the contrast agent, resulting in an overestimation of CBF 31 .…”
Section: Discussionmentioning
confidence: 99%
“…31 tASL can avoid this problem since no contrast agent is injected. Lin et al 17 performed tASL examination on patients undergoing CEA surgery and found that the CBF of the affected side and the contralateral side both increased after the operation, allowing a more comprehensive evaluation of the surgical effect. According to the literature 13 and our results, tASL is more reliable for monitoring changes in CBF after surgery than solely relying on the degree of stenosis to assess these changes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…While the feasibility of SS‐pCASL has been shown previously in a number of clinical applications, SNR still remains a challenge . Pseudo‐continuous labeling is well known to be a low SNR technique.…”
Section: Introductionmentioning
confidence: 99%